دەوڵەتى کوردستان لە چوار پێشنیاردا بۆ رۆژهەڵاتى ناوەراست - كریم, هێرش عبدالله حمه‌ (Sulaimani Journal for Humanities, 2018)
Summary The Sykes-Pico Agreement in 1916 established the current map of the Middle East. However, until this moment, a century past, the international borders are still sought to be concreted and defined. For this reason, there are still proposals to change and alter the map of the Middle East in a way that will bring peace and stability to the region. There is a commonality between most of the proposals, that is, the emergence and foundation of the state of Kurdistan in the Middle East in the near future. This research “The State of Kurdistan in Four Proposal for The Middle East”, has aimed at answering the question of; where is Kurdistan’s position in all of these proposals of the Middle East. In conclusion of the proposals studied, the state of Kurdistan has had the ability to put itself into the Middle East, in a way that shows it is not just a normal state, but a state which would play a role in balancing the conflicts and tensions of the region.